2013
DOI: 10.2337/db12-1692
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of HKDC1 and BACE2 as Genes Influencing Glycemic Traits During Pregnancy Through Genome-Wide Association Studies

Abstract: Maternal metabolism during pregnancy impacts the developing fetus, affecting offspring birth weight and adiposity. This has important implications for metabolic health later in life (e.g., offspring of mothers with pre-existing or gestational diabetes mellitus have an increased risk of metabolic disorders in childhood). To identify genetic loci associated with measures of maternal metabolism obtained during an oral glucose tolerance test at ∼28 weeks’ gestation, we performed a genome-wide association study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
158
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(165 citation statements)
references
References 49 publications
(61 reference statements)
6
158
0
1
Order By: Relevance
“…We also constructed a GRS based on 5 SNPs (GRS 5 ) associated with fasting glucose in pregnancy (rs560887, rs6235, rs1260326, rs7936247 and rs4841132). 23 GRS 5 explained about 6.6% of fasting glucose variance. Finally, we constructed another GRS with all glycemic SNPs genotyped (GRS 21 ).…”
Section: Instrumental Variable For Fasting Glucosementioning
confidence: 98%
See 3 more Smart Citations
“…We also constructed a GRS based on 5 SNPs (GRS 5 ) associated with fasting glucose in pregnancy (rs560887, rs6235, rs1260326, rs7936247 and rs4841132). 23 GRS 5 explained about 6.6% of fasting glucose variance. Finally, we constructed another GRS with all glycemic SNPs genotyped (GRS 21 ).…”
Section: Instrumental Variable For Fasting Glucosementioning
confidence: 98%
“…[22][23][24][25] To build our first IV, we selected 10 of these SNPs to construct our genetic risk score (GRS 10 ) representing maternal glucose levels based on the variance explained (each SNP r 2 0.002 in association with maternal fasting glucose in Gen3G). We observed that a higher GRS 10 was associated with higher maternal fasting glucose at 2nd trimester and found that the moderate association was highly significant by statistical testing (b G1 D 0.046 mmol/L of maternal fasting glucose per additional risk allele; SE D 0.007; P D 7.76 £ 10 ¡11 ; N D 467; Fig.…”
Section: Two-step Epigenetic Mrmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, variants in G6PC2 have been consistently associated with FG levels, whereas their contribution to T2D risk remains controversial. In particular, the rs560887 SNP is one of the strongest signals associated to FG (and related traits), and one of the most commonly replicated in large-scale analyses [3][4][5][6][52][53][54]. Moreover, the variant was shown to be functional and to modulate G6PC2 pre-mRNA splicing [7].…”
Section: Discussionmentioning
confidence: 99%